Nutritional and Organoleptic Analysis of Tilapia Roulade As a Local Complementary Food Innovation to Prevent Stunting in Toddlers - Umamah, Nisrina Azzah; Arief, Ria Qadariah; Lusiana, Nova (International Conference on Sustainable Health Promotion, 2025)
Fish was a valuable source of animal protein, rich in essential nutrients, and had great potential as a complementary food product. However, limited innovation in modified fish-based products contributed to the low acceptance of fish among children. This study was conducted to evaluate the nutritional content and organoleptic properties of tilapia (Oreochromis mossambicus) roulade as a locally based complementary food product. The nutritional composition of the tilapia roulade was analyzed using the Indonesian Food Composition Table (DKBM). Organoleptic evaluation was performed by panelists through a hedonic test, which assessed parameters including color, aroma, taste, texture, appearance, and overall acceptability. The analysis showed that each serving of tilapia roulade contained 162.7 kcal of energy, 9.96 g of carbohydrates, 15.1 g of protein, and 6.52 g of fat, along with a complete profile of vitamins. Results from the organoleptic test indicated a high level of acceptance across all sensory attributes. These findings suggested that tilapia roulade, as a locally sourced innovation, had strong potential as an acceptable and nutritious complementary food product to support stunting prevention efforts.